DECISION SUPPORT SYSTEM FOR CATTLE LOCATION SUITABILITY USING THE AHP METHOD - Marwan; Nurmalinda Utami Siregar; Umar Abdul Gani Tarigan; Sekar Ayu Irawan (Pena Cendekia Insani, 2021)
Currently, many breeders do not meet the criteria for the placement ofappropriate and correct livestock locations in the manufacture of cattle pens.This causes the cows to become sick often and many die, because the cages arenot clean and healthy. Cages that are not clean and healthy also have an impacton the community, especially those around the livestock location. The AHPmethod is used as a decision support system to determine the location of cattlethat are suitable for farmers, especially in the Deli Serdang area. The results ofdetermining the location of suitable livestock are based on parameters or criteriasuch as ecological parameters, institutions, human resources, infrastructuredevelopment, and technology and regional development.